Pemanfaatan Batu Sungai Batupapan Kabupaten Luwu Dalam Campuran Laston Lapis Pondasi - Yorlan Victor Padatu; Alpius; Monika D.M Palinggi (Program Studi Teknik Sipil UKI Paulus-Makassar, 2021)
The availability of stones in the Batupapan River and when examined meets the Highways Standard to be used as a mixture of pavement for paving so that the people around Telluwanua District, Luwu Regency and Palopo City can use it to improve the community's economy and support the availability of materials for the government. The purpose of this study was to determine the use of Batupapan River Stones in Telluwanua Subdistrict, Luwu Regency as a mixture of Laston Layer Foundation (AC-BC) by testing the characteristics of the material used and testing the resistance to water immersion by analyzing the remaining Marshall Stability. The method used is an experimental method that is carried out at the Road and Asphalt Laboratory of the Civil Engineering Study Program of Paulus Indonesia Christian University. The results of testing the characteristics of the Laston Lapis mixture of the foundation and the characteristics of the asphalt mixture are all in accordance with the specifications or standards used. For conventional Marshall testing the characteristics, stability, fluidity, VIM, both VMA and VFB meet all specifications issued by the Director General. The results of the Marshall Bina Marga immersion test in the general specifications of Bina Marga Bina Marga 2018 Division 6 and the remaining Marshal Stability Value (SMS) used below the optimum asphalt content (KAO) of 5.00% is 98.04%, so it can be said that the general specifications on Bina Marga 2018, because the value is not less than 90%.